Solid Electrolyte Interface Growth Fault Modeling for Battery State of Health Simulation - Shao, Junya; Chow, Mo-Yuen; Tan, Zhiping; Jin, Huiqin (IEEE International Conference on Industrial Technology (Online), 2025)
In this study, a solid electrolyte interface growth fault simulator is developed based on pseudo-2-dimensional model and verified using the state of health data from UCL cycling test. Considering the regeneration in capacity, the simulation is realized in 5 separate segments corresponding to different battery aging conditions. The infinity norm, the mean absolute error and the root mean square error of state of health simulation are turned out to be no more than 0.009657, 0.002227 and 0.003243 respectively. And the parameter variation at different aging segments is finally analyzed to be consistent with microscopic electrochemical mechanisms.